Factors determining the occurrence and number of bacteria of the genus Azotobacter in the soil environment - Kozieł, Monika (Polish Journal of Agronomy, 2023)
Bacteria belonging to the genus Azotobacter are microorganisms commonly found in various soils all over the worldand capable of fixing atmospheric nitrogen. The biological ni-trogen fixation (BNF) process annually supplies approximately 140–170 million tons of this element to the nitrogen cycle, whichis of great importance from an ecological and practical point ofview. Although the efficiency of atmospheric nitrogen fixation byAzotobacter spp. is not high and amounts to 20 mg N per 1 gof glucose used, these bacteria are sensitive to various environ-mental factors, including soil reaction, contents of organic matter,soil humidity or nutrient content, and their abundance in soils issmall. These bacteria secrete numerous biologically active sub-stances into the soil environment, which have a beneficial effecton the development of plants, which from the ecological pointof view plays an important role in the functioning of agriculturalecosystems. An additional advantage of bacteria belonging to thegenus Azotobacter, which speaks for their use in agriculture, isthe ability to produce antifungal compounds and solubilization ofinsoluble phosphates. Research on Azotobacter spp. proves thatthe concentration of hydrogen ions (pH) is a significant factorwhich determines the presence of this group of bacteria in thesoil environment. Many other soil properties have a large impacton the presence and development of this important agriculturalgroup of bacteria. The aim of the work was to systematize the knowledge on theknown occurrence conditions and ecological relationships andinteractions between environmental factors and the presence andabundance of Azotobacter bacteria in soils.